Possibilities of long-range forecast of weather conditions over the Antarctic peninsula - Martazinova, V. F.; Maderich, V.S.; Tymofeyev, V. Y.; Ivanova, E. K. (Ukrainian Antarctic Journal, 2009)
Developed by us in 1998 the method of long-range weather forecast for the moderate latitudes of Northern hemisphere is based on two-month similarity of atmospheric circulation which is well revealed by the traditional method of analogues of one season. That is why similarity of atmospheric processes in the non-tropical latitudes of Southern hemisphere was also explored by the method of traditional analogue. Similarity between the processes of successive days on the fixed territory taking into account the coincidence of all geographical coordinates allowed to set in Southern hemisphere two-month quasi-periodicity of large-scale and consequently regional atmospheric circulation. Taking into account found out the period of quasi-periodicity of regional atmospheric circulation of the Antarctic Peninsula near 60 days in a summer period and near 70 days in a winter period the forecast scheme of anomaly of average monthly temperature of air is developed. The forecast scheme of anomaly of average monthly air temperature for the area of Akademik Vernadsky Station is developed with monthly earliness with the aim of equations of linear regression. The anomaly of average monthly air temperature of initial month is used in equation of linear regression as prediktor. The estimation of forecast scheme was executed on dependent material of separate years and showed success of the offered method of forecast of average monthly air temperature for Akademik Vernadsky Station. For the improvement of estimation of extreme values of temperature above the Antarctic Peninsula and at Akademik Vernadsky Station the scheme of long-range forecast of average monthly air temperature was complemented by auxiliary equations, that allow to calculate extreme values. On the whole it is possible to mark that found out atmospheric circulation conformities of near two-month quasi-periodicity for the moderate latitudes of Southern hemisphere can be basis for development of method of long-range forecast of atmospheric circulation and weather conditions for the territory of Antarctic Continent.